2008
DOI: 10.1523/jneurosci.5331-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Clutch between the Actin Flow and N-Cadherin Adhesions Drives Growth Cone Migration

Abstract: The adhesion molecule N-cadherin plays important roles in the development of the nervous system, in particular by stimulating axon outgrowth, but the molecular mechanisms underlying this effect are mostly unknown. One possibility, the so-called "molecular clutch" model, could involve a direct mechanical linkage between N-cadherin adhesion at the membrane and intracellular actin-based motility within neuronal growth cones. Using live imaging of primary rat hippocampal neurons plated on N-cadherin-coated substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
144
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(150 citation statements)
references
References 57 publications
6
144
0
Order By: Relevance
“…Thus, the cadherin/catenin complex may be a constitutive membrane anchor for the cortical actomyosin cytoskeleton. In this context, it is noteworthy that cadherin lateral mobility in the plasma membrane depends on the catenin-binding region of the cytoplasmic domain even outside of cell-cell contacts and is regulated by the underlying cortical actin cytoskeleton (54,55). That the cadherin/catenin complex functions in membrane-to-cortex attachment may explain why this complex is important for regulating macropinocytosis in contact-free protruding membranes (56), single-cell wound closure in Drosophila (57), and plasma membrane blebbing during early embryogenesis in zebrafish (58).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the cadherin/catenin complex may be a constitutive membrane anchor for the cortical actomyosin cytoskeleton. In this context, it is noteworthy that cadherin lateral mobility in the plasma membrane depends on the catenin-binding region of the cytoplasmic domain even outside of cell-cell contacts and is regulated by the underlying cortical actin cytoskeleton (54,55). That the cadherin/catenin complex functions in membrane-to-cortex attachment may explain why this complex is important for regulating macropinocytosis in contact-free protruding membranes (56), single-cell wound closure in Drosophila (57), and plasma membrane blebbing during early embryogenesis in zebrafish (58).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, PDGF induces the translocation of cortactin to podosomes via the GAP BPGAP1 and Rac1, indicating that PDGF receptor is involved in the formation of podosomes [226,227]. As described above, PDGFR colocalizes with N-cadherin in membrane ruffles, and both N-cadherin and cortactin are found in the growth cones of emerging neuronal axons and exert a crucial role in neuron guidance [81,228]. The co-localization of cortactin with the Ncadherin/NCAM/FGFR complex and NCAM-mediated FGFR signaling have been shown to contribute to neurite outgrowth [95].…”
Section: Invadopodia and Their Role In Emtmentioning
confidence: 70%
“…Like its epithelial counterpart, N-cadherin is connected via α-catenin and β-catenin to the cytoskeleton and functions as both a mechanical cell adhesion component and a signaling molecule. Recently, it has been reported that during neurite extension the traction forces generated by retrograde actin flow are directly transmitted to N-cadherin adhesions, thereby mechanically linking N-cadherin with the formation of motile structures [81]. Interestingly, the authors show that the mechanical engagement of Ncadherin induces local actin polymerization and thereby ensures the integrity of the adhesion complex.…”
Section: The Cadherin Switch and Its Consequencesmentioning
confidence: 99%
“…Our study highlights intercellular adhesions' ability to impact cell-ECM force generation, which allows for bidirectional feedback between cell-cell and cell-matrix forces. Indeed, tension at cadherin junctions (13,54) is known to elicit cell-signaling events and actin dynamics (52, [55][56][57][58] and contribute to collective cell migration (26,59,60). In light of these prior results on integrin-cadherin feedback, it is somewhat surprising that a minimal physical model can capture the observed dependence of cell-matrix forces on the strength of cadherin-mediated cell-cell adhesions.…”
Section: Discussionmentioning
confidence: 99%